Natural history notes on worker size, colony size, and nest structure of Azteca muelleri Emery, 1893 (Hymenoptera: Formicidae) in Cecropia glaziovii (Rosales: Urticaceae) from the Atlantic Forest - Nagatani, Victor; da Silva, Nathalia S.; Albuquerque, Emília Z.; Gaglioti, André L.; Morini, Maria S. C. (Entomological Communications, 2021)
Mutualistic association between Azteca Forel, 1878 ants and Cecropia Loefl. plants are one of the most studied interactions in Neotropics, however, natural history studies of Azteca species still poorly investigated due to the great effort required to conduct detailed descriptive studies. Here, we describe biological aspects of Azteca muelleri Emery, 1893 nesting in Cecropia glaziovii Snethl. in a fragment of Atlantic Forest, addressing (a) colony size; (b) nest distribution on the tree; and (c) worker and queen morphometrics. We collected two C. glaziovii saplings and counted characteristics of the nests and plants. We randomly selected 140 workers to measure and to determine whether intraspecific polymorphism occurs. Workers, immatures, and mealybugs were present in all hollow internodes of plant, and a queen was found. We found isometric morphological variation in A. muelleri. Our study provides new data to understand the biology of A. muelleri nesting in C. glaziovii, one of the most species-rich genera of arboreal ants known for the neotropics.